COMPARISON OF THREE PROGNOSTIC SCORES (PRISM, PELOD AND PIM 2) AT PEDIATRIC INTENSIVE CARE UNIT UNDER PAKISTANI CIRCUMSTANCES - Qureshi, Ahmad Usaid; Ali, Agha Shabbir; Ahmad, Tahir Masood (Journal of Ayub Medical College Abbottabad, 2007)
Background: To compare the performance of the Pediatric Risk of Mortality (PRISM), the Pediatric Index of Mortality 2 (PIM 2) and Pediatric Logistic Organ Dysfunction (PELOD) scores at general pediatric intensive care unit in a developing country setting, investigating the relation between observed and predicted mortality. Method: A contemporary cohort study was undertaken at Pediatric Intensive Care Unit (PICU), Children’s Hospital, Institute of Child Health, Lahore, Pakistan. 131 consecutive admissions fulfilling the inclusion criteria were enrolled in the study. PRISM, PIM 2 and PELOD calculations were performed as set out by original articles, using the published formulae. Statistical analysis included Standardized Mortality Rate (SMR), Hosmer Lemeshow goodness of fit test, receiver operating curve (ROC) characteristics and Spearman’s correlation test. Results: 139 patients were admitted to PICU. 38 presented exclusion criteria. 29 (28.7%) patients died. Estimated mortality was; PRISM: 19.7(19.5%), PIM: 21.01(20.5%) and PELOD:18.4(18.3%). SMR was 1.47 (SD ± 0.19), 1.4 (SD ± 0.19) and 1.57 (SD ± 0.19), respectively. PRISM had better calibration (x2 = 7.49, p = 0.49) followed by PIM 2 (x2 = 9.65, p = 0.29). PIM 2 showed best discrimination with area under ROC = 0.88 (0.81-0.94) followed by PRISM 0.78 (0.67-0.89) and PELOD 0.77 (0.68-0.87). Spearman’s correlation r between PRISM and PIM 2 returned 0.74 (p < 0.001). Conclusion: PRISM as well as PIM 2 is validated for PICU setting in Pakistani circumstances. PELOD performed poorly. PIM 2 has advantages over PRISM for stratification of patients in clinical trials. Key words:Prognostic score; PRISM; PIM 2; PELOD; Mortality